Five -Factor Model (FFM) of Personality Toward Adoption of Innovative Purchasing Indonesia Consumer Across Generation - Triwijayati, Anna (Husnayain Business Review, 2024)
Purpose – This paper seeks to test the impact of the five personality factors on innovative behaviour in purchasing Indonesian consumers across generations. Methodology/approach – Quantitative methods were used in this research and used survey techniques. The survey was carried out by distributing questionnaires to 1000 Indonesian consumer respondents from 34 provinces. The response rate was 878 people/questionnaire analysed. Findings – It was found that the personality traits Openness to Experience and Extraversion have a positive and significant effect on the adoption of purchasing innovations among Gen Z, Y consumers and total consumers. The Conscientiousness characteristic has a positive effect and Neuroticism has a significant negative effect on the Adoption of purchasing innovations in generation. Novelty/value – Therefore, understanding the characteristics of innovators is important for companies because this group of consumers determines the success of the diffusion of product innovation.